Literature Review: The Effectiveness of Group Guidance Services with Discussion Techniques in Increasing Self-Confidence of Middle School Students - Daema Rizky Aulia; Evi Winingsih (Journal of Cultural Guidance and Counseling, 2025)
This literature review focuses on the contribution of group guidance services using discussion techniques in increasing students' self-confidence at the secondary school level. Self-confidence is an important aspect of students' psychological development that influences learning engagement and social relationships. The method used is a literature review by examining various scientific sources, such as journals, books, and previous research results relevant to the topic. The results of the study indicate that group guidance services using discussion techniques are effective in providing opportunities for students to express opinions, explore their potential, obtain social support, and build positive attitudes towards themselves. Therefore, this service is recommended for optimal implementation as part of the guidance and counseling program in secondary schools to support the increase in students' self-confidence.